Real-time dual-channel speckle interferometry based on an improved dual-observation configuration with spatial phase-shifting. (May 2021) - Gu, Guoqing; Pan, Yun; Qiu, Chengchun; Zhu, Chengjie
Highlights: Dual-channel speckle interferometry is developed for multi-parameter measurements. Spatial carrier phase-shifting technique is used for real-time phase retrieval. Dual-channel speckle interferometry is proved by dynamic measurement applications. Abstract: This paper develops a real-time dual-channel speckle interferometry system based on an improved dual-observation configuration to address the issue of simultaneous measurement of the out-of-plane displacement and slope. A dual-observation configuration combined with an additional light path is used to provide the possibility to create two measurement channels corresponding to the out-of-plane displacement and slope, respectively. In the system, two symmetric observation light paths are slightly displaced from each other by a deliberate tilt of the plane mirror to introduce an adjustable lateral shear. One of the two observation beams is shared by both measurement channels to improve the system's stability. Besides, using the spatial carrier phase-shifting technique induced by multi-aperture, the real-time phase retrieval is achieved for simultaneous measurement of the dynamic out-of-plane displacement and slope. Both the experimental investigation and the non-destructive testing (NDT) application are finally presented to demonstrate the feasibility and effectiveness of the proposed system.